Using mHealth App to Support Treatment Decision-Making for Knee Arthritis: Patient Perspective. Issue 2 (20th April 2017) - Zheng, Hua; Tulu, Bengisu; Choi, Wonchan; Franklin, Patricia
Introduction: Mobile health (mHealth) technology can be used to integrate into medical decisionmaking for patients with advanced knee arthritis. We explored patient preferences on content and design of a mobile health app to facilitate daily symptom capture and summary feedback reporting, in order to inform treatment decisions, including use of total knee replacement surgery (TKR). Methods: Patient focus groups were conducted to gather requirements for mHealth app development and to refine the design and content of the app. Clinician (physical therapist, surgeon) interviews were conducted to understand clinician expectations from the summary trend report generated by the app. Results: Sixteen patients attended focus groups with an average age of 67 and 63% female, and three clinicians participated in clinician interviews. The preliminary findings revealed that the patients preferred easy tap user interfaces to multitap or slider methods, and vertical question layout to horizontal orientation. Patients liked to be engaged by progress feedback reports and educational tips. Both patients and clinicians found a trended outcome summary report helpful which provides more precise details on whether and how the symptoms are changing over time. Discussion: User input can inform the design and implementation of mHealth technology to meet patient needs for their treatment decisions. Patient priorities must be considered through patient-centered app design.